Analysis Of Bodrex Brand Tows As A Marketing Strategy Of Head Disease Drugs - Asep Sugara; Mustofa Mustofa; MD Sukamto (Fakultas Bisnis, 2020)
His study aims to determine the company's external factors, namely opportunities and threats as well as internal factors of the company, namely strengths and weaknesses, as the basis for the company's strategy formulation in marketing headache products with the Bodrex brand. By using the TOWS analysis company strategy companies are advised to use a strategy that is aggressive (SO), by memafaatkan distribution channels in order to improve marketing by utilizing Bodrex that has become a brand image in the community and m enggunakan advertising funds to increase its frequency by utilizing a number of TV stations.